PARADOKS NORMA SOSIAL DALAM KEPATUHAN SERTIFIKASI ISPO: BUKTI DARI AKUNTANSI KEPERILAKUAN - Antonius Grivaldi Sondakh; Lili Safrida (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2026)
This study challenges the foundational assumption in behavioral accounting that social norms promote compliance. It investigates a paradoxical possibility: under certain conditions, social norms may inhibit compliance. Drawing on the theory of planned behavior, this research examines how social norms, conservation beliefs, and self-efficacy influence smallholders' intention to adopt Indonesian Sustainable Palm Oil (ISPO) certification. Survey data from 143 smallholders in South Kalimantan were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal a social norms paradox: perceived community pressure negatively influences certification intention. Conservation beliefs also exhibit a negative effect, indicating value-control misalignment when certification is perceived as disconnected from substantive outcomes. In contrast, self-efficacy positively influences intention. This study identifies boundary conditions for subjective norms and introduces the concept of value-control misalignment to explain resistance among environmentally committed actors.